2019
DOI: 10.36941/ajis-2019-0028
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Household Food Expenditure in a Cassava Growing Village in Southeast Sulawesi

Abstract: The study aimed to analyze the factors affecting food consumption expenditure among cassava growing households in Southeast Sulawesi Province, Indonesia. The study was carried out in Lapodi village, Pasarwajo subdistrict, Buton district, from April to July 2018. The primary data were collected from 32 respondents selected using a random sampling method. The data were analyzed using descriptive statistics and the multiple regression method. The study results showed that households spent a very high percentage o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 11 publications
1
10
0
2
Order By: Relevance
“…In South Sulwesi province, cigarette has become necessity for men hence the budget for smoking constitutes 3 biggest spending in household in addition to meal (rice and cassava) and protein (fish and egg). Each day they can smoke 10 to 20 cigarettes in average 11 . Indonesian smokers consume average 12,8 cigarettes.…”
Section: Discussionmentioning
confidence: 99%
“…In South Sulwesi province, cigarette has become necessity for men hence the budget for smoking constitutes 3 biggest spending in household in addition to meal (rice and cassava) and protein (fish and egg). Each day they can smoke 10 to 20 cigarettes in average 11 . Indonesian smokers consume average 12,8 cigarettes.…”
Section: Discussionmentioning
confidence: 99%
“…Households of married men and women in Malaysia (Yusof & Duasa, 2010) and the influence of urban agricultural households on food security status in Ibadan (Yusuf et al, 2015). Likewise, with the expenditure of staple food consumption in Ika (Ndubueze-Ogaraku et al, 2016), the availability of calories and the diversity of agricultural household food in Bangladesh (Sraboni et al, 2014), household food security among urban migrant farmers in Delhi, Jakarta, and Quito (Diehl et al, 2019), as well as food consumption expenditure on cassava plants in Southeast Sulawesi Province (Zani et al, 2019). However, research on household expenditure with food and non-food consumption patterns on farmers and farmer womens has never been carried out.…”
Section: Introductionmentioning
confidence: 99%
“…though it is expensive. Households in Southeast Sulawesi spend more money on food (89.84%) than non-food (10.16%), and food expenditure is dominated by starchy staples, fish and eggs, while consumption of vegetables, fruit, and low milk(Zani et al, 2019). Furthermore, it was explained that most households that grow cassava have a low level of welfare, and their food consumption is not diverse and of good quality.…”
mentioning
confidence: 99%
“…In Indonesia, the overall consumption of fruits is lower than the recommended level. Saediman et al [4] and Zani et al [5] reported that the low-income households still give more priority to quantitative adequacy of foods than to its nutritional content and quality. Based on Dietary Diversity Score, Indonesians tend to eat more cereals and fewer tubers and roots, meat, vegetables, and fruits [6].…”
Section: Introductionmentioning
confidence: 99%